Ergonomic assessment of natural rubber processing in plantations and small enterprises (2016)
(Eng) This exploratory study used OWAS (Ovako Working Posture Analysing System) to analyze the working postures of natural rubber tappers and rubber industry workers. A community of natural rubber farmers of Tarazá and five small companies of Medellín and Itagüí, all of them allocated in Antioquia-Colombia, participated in this study. Processes were analyzed in-situ and videotapes of activities were recorded for carrying out a movement study. For an overall distribution of trunk postures, OWAS identified that a bent and twisted trunk posture which fell into action category 4, was the major poor posture for rubber tappers and rubber industry workers. This study also identified that latex tapping, latex collection, mixing in two roll mills and metallic molds operation were the four activities in which the major working posture risks were observed. It was found that reduction of posture risks in natural rubber production chain requires designing and implementing plans considering organizational culture, socio-economic and sociodemographic factors of natural rubber farmers and small rubber manufacturing industries, besides the use of some useful tools that reduce the handling of heavy loads